2010
DOI: 10.1088/1748-6041/5/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis and characterization of hydroxyapatite and fluorhydroxyapatite nano-size powders

Abstract: Pure hydroxyapatite (HAp) and fluoride-containing apatite powders (FHAp) were synthesized using a hydrothermal method. The powders were assessed by x-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscope (SEM) and F-selective electrode. X-ray diffraction results revealed the formation of single phase apatite structure for all the compositions synthesized in this work. However, the addition of a fluoride ion led to a systematic shift in the (3 0 0) peak of the XRD pattern as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 15 publications
0
40
1
1
Order By: Relevance
“…Furthermore, with the increasing degree of fluoridation, the intensity of the OH characteristic band at 3573 cm −1 became weaker, while the other band at 3544 cm −1 attributed to hydrogen interacting with fluorine became stronger [25, 26]. Similarly, another major change in the FTIR spectra of FPHA was that the absorption band attributed to OH around 634 cm −1 disappeared, and was replaced by another band around 742 cm −1 attributed to OH interacting with fluorine [26, 27], which was further evidence for fluoride incorporation (figure 2(c)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, with the increasing degree of fluoridation, the intensity of the OH characteristic band at 3573 cm −1 became weaker, while the other band at 3544 cm −1 attributed to hydrogen interacting with fluorine became stronger [25, 26]. Similarly, another major change in the FTIR spectra of FPHA was that the absorption band attributed to OH around 634 cm −1 disappeared, and was replaced by another band around 742 cm −1 attributed to OH interacting with fluorine [26, 27], which was further evidence for fluoride incorporation (figure 2(c)).…”
Section: Resultsmentioning
confidence: 99%
“…The results of FTIR in the present study further confirmed that fluoride substituted for hydroxyl groups in the apatite crystal structure. Also, the fluoride substituted for hydroxyls causes the shift of the reflection in the XRD pattern [25, 27]. Previous studies on the dissolution behavior of synthetic FHA were mainly based on deionized water [16, 18, 26], physiological saline solution [17, 25] and simulated body fluid [28], which could not simulate the in vivo environment of implant biomaterial appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds are called fluorhydroxyapatites (FHA) (Nikcevic et al 2004;Montazeri et al 2010;Zhu et al 2012) or hydroxyfluorapatites (HFA) (Rodríguez-Lorenzo et al 2003;Azami et al 2012) and described with a chemical formula Ca 10 (PO 4 ) 6 (-OH) 2-x F x , where 0 \ x \ 2. If the F/OH ratio is either uncertain or not important, the chemical formula of FHA and HFA is often written as Ca 10 (PO 4 ) 6 (F,OH) 2 .…”
Section: Fa (Or Fap)mentioning
confidence: 99%
“…Fluorapatite is a bioactive compound with an apatite-like structure, in which OH groups have been substituted by fluorine ones. Furthermore, its crystalline structure is more stable than hydroxyapatite, which is an important issue where bioactivity receives attention based on crystalline stability [1][2][3]. Similarity between hardness of fluorapatite-based glass-ceramics and tooth enamel is another advantage that makes them new candidates for substitution of hydroxyapatite in restorative dentistry [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Following the precipitation of apatite in these droplets, changing the composition of the residual glass phase leads to the precipitation of mullite [4,5,8]. In these specimens fluorapatite is responsible to link to the tooth enamel and bone [3] and mullite induces adequate mechanical properties [10]. The latter phase plays a key role in biocompatible glass-ceramics since they are mostly planned to use in the stress bearing areas [2].…”
Section: Introductionmentioning
confidence: 99%